What Type of Consumption Induces or Alleviates Consumer Psychological Distress? Evidence From the COVID-19 Pandemic in China - Wang, Yong; Chen, Shuo; Yang, Dandan; Li, Yang (Frontiers in Psychology, 2021)
Even though the corona virus disease (COVID-19) has limited consumption, individuals continue to plan post-pandemic consumption activities to get rid of the stress caused by consumption repression. Building on Maslow’s theory of needs and Herzberg’s two-factor theory, our research categorizes consumption into fundamental (“must have” products that fulfill the physical need of individuals), hygiene (maintaining the security needs of consumers), and motivational consumption (enhancing individuals’ well-being). Based on empirical data of purchase behavior and consumption expectation before, during, and after the pandemic in China, we identify how consumption repression induces psychological stress—via a sense of feeling threatened, lacking control, or lacking freedom—and how the expectation of future consumption alleviates that stress. Results show that fundamental consumption leads to psychological stress; hygiene consumption can both result in and reduce stress; and motivational consumption can reduce stress. Our findings provide new insights into the relationship between consumption and psychological stress through new theoretical formulations. The results can be applied by marketers attempting to understand purchase decision-making and by policy makers supporting both citizens and commerce during social emergencies.